2012
DOI: 10.1002/jmri.22830
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of central nervous system viral diseases

Abstract: Viral infections of the central nervous system (CNS) are commonly encountered and there has been continued emergence of new neurotropic viruses which are being frequently recognized. These may present clinically as encephalitis, meningitis, encephalomyelitis, and encephalomyeloradiculitis. The clinical manifestations are usually nonspecific and diagnosis is usually based on the laboratory investigations. Imaging plays a role in its early detection and at times suggests the specific diagnosis that may help in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 75 publications
(87 reference statements)
1
15
2
1
Order By: Relevance
“…However, maximal viral loads have been found in the basal ganglia, in particular in the caudate and globus pallidus, as well as in the medial temporal lobes, the hippocampus, and the frontal lobes 53, 54 The reason for this predilection is not clear, though several viral encephalitides that are spread hematogenously also target these areas preferentially 55 Recent studies suggest that there is a substantial viral load in the meninges as well where there is a rich collection of macrophages 51 . These meningeal macrophages also get infected with HIV and this may be a yet important reservoir for the virus.…”
Section: Regional Compartmentalization Of Hiv In Brainmentioning
confidence: 99%
“…However, maximal viral loads have been found in the basal ganglia, in particular in the caudate and globus pallidus, as well as in the medial temporal lobes, the hippocampus, and the frontal lobes 53, 54 The reason for this predilection is not clear, though several viral encephalitides that are spread hematogenously also target these areas preferentially 55 Recent studies suggest that there is a substantial viral load in the meninges as well where there is a rich collection of macrophages 51 . These meningeal macrophages also get infected with HIV and this may be a yet important reservoir for the virus.…”
Section: Regional Compartmentalization Of Hiv In Brainmentioning
confidence: 99%
“…35 However, the MRI changes are non-specific in most patients with viral encephalitis and do not enable any definite conclusions to be drawn about the causative organism. 34 This patient's MRI scan showed bilateral high intensity signal changes in the peritrigonal and occipital white matter, as well as adjacent to the body of each lateral ventricle and the temporal horns ( fig 2). …”
Section: Discussionmentioning
confidence: 79%
“…In most cases of viral encephalitis the cranial MRI images show diffuse hyperintense changes in varying regions of the brain parenchyma on T2 weighted scans. 34 In some instances the MRI images can also provide clues about the causative organism. One example is herpes simplex virus encephalitis, which typically affects the inferior and medial aspects of the temporal lobes, with bilateral involvement being more common than unilateral involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Acute CNS viral infections may produce a pattern of cortical DWI and T2 signal abnormalities with relative sparing of white matter similar to that seen in our patients. 17 Viral coinfection in patients with CM has only rarely been studied. A case series of 49 Kenyan children with clinically defined CM revealed that 9% of the studied patients had CNS herpesvirus or enterovirus coinfection.…”
Section: Discussionmentioning
confidence: 99%
“…In five (83%) of six of the children with T2 signal abnormalities and in all (five of five or 100%) of the children with DWI abnormalities in the corpus callosum, the splenium was the primary area affected. The splenium is often preferentially involved in children with viral encephalitis 17,23,24 and Salmonella enteritidis-associated encephalopathy, 25,26 although other studies postulate that these findings are non-specific and may be caused by seizures or metabolic abnormalities in addition to CNS infections. 27 The high proportion of splenial predominance in children with callosal abnormalities in our study group further supports the possibility that at least some children with retinopathy-negative CM may have an acute systemic or CNS viral coinfection.…”
Section: Discussionmentioning
confidence: 99%